2019
DOI: 10.1002/cpt.1570
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Effects of a γ‐Secretase Modulator, PF‐06648671, on CSF Amyloid‐β Peptides in Randomized Phase I Studies

Abstract: γ-Secretase modulators (GSMs) represent a promising therapy for Alzheimer's disease by reducing pathogenic amyloid-β (Aβ) peptide production. Three phase I studies (NCT02316756, NCT02407353, and NCT02440100) investigated the safety/tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of the oral GSM, PF-06648671. A PK/PD indirect-response model was developed (using biomarker data) to simultaneously characterize differential effects of PF-06648671 on multiple Aβ species in cerebrospinal fluid (CSF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…6 ). A study from Pfizer investigated PF-06648671, derived from bicyclic pyridinones, in three phase I trials [ 70 ]. In 14 day single-dose and multiple-ascending daily doses in healthy normal subjects, the oral GSM was well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…6 ). A study from Pfizer investigated PF-06648671, derived from bicyclic pyridinones, in three phase I trials [ 70 ]. In 14 day single-dose and multiple-ascending daily doses in healthy normal subjects, the oral GSM was well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…R-flurbiprofen has weak in vitro GSM activity and, although safe, did not show efficacy in phase 3 human trials ( Green et al, 2009 ). More recent discovery efforts have yielded several newer GSMs that were tested in early-phase clinical trials, primarily single ascending dose (SAD) and multiple ascending dose (MAD) phase 1 studies, and yet none of these has moved beyond these primary safety evaluations ( Ahn et al, 2020 ; Kounnas et al, 2019 ; Soares et al, 2016 ; Toyn et al, 2016 ; Yu et al, 2014 ). Lack of clinical development of prior GSM drug candidates could be due to the lack of establishing a suitable therapeutic index for dosing regimens able to substantially lower CSF Aβ42 levels without eliciting significant adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Another MAD study involved the GSM NGP555, which showed a trend toward increasing ratios of Aβ37/Aβ42 and Aβ38/Aβ42 in CSF at doses of 200 mg and 400 mg, but without demonstrating statistical significance ( Kounnas et al, 2019 ). The most recently published clinical studies involved both SAD and MAD regimens with the GSM PF-06648671 ( Ahn et al, 2020 ). Study designs differed between SAD and MAD stages.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited amount of CSF A␤ data collected (only at baseline and a single trough measurement at steady state), the parameters for CSF A␤ turnover rates were fixed to 0.084/h for A␤ 1-40 and 0.12/h for A␤ 1-42 , which were estimated in a separate, PK/PD study with serial CSF collections [25]. Due to the similarity in study populations, it was assumed that A␤ dynamics in the PK/PD model described here would be the same as those from the separate PK/PD study [25]. The estimated exposure-response relationship was specific to PF-06751979, based on the current multiple-dose data.…”
Section: Pk/pd Modeling For Csf Aβ 1-40 and Aβ 1−42mentioning
confidence: 99%